Solution of optimal control problem for magnetoelectric drive with oscillatory motion - A. A. Tatevosyan (Омский научный вестник)
The mathematical formulation and solution of optimal control problem for magnetoelectric drive of machines with oscillatory motion of the working body are given. On the basis of the obtained solution, the algorithm for optimizing design of magnetoelectric motors for a given law of rotor motion is constructed under condition of providing the maximum electromagnetic force produced by the engine and the minimum mass of the active materials used.